2013
DOI: 10.1002/chem.201300649
|View full text |Cite
|
Sign up to set email alerts
|

Precise Size Control over Ultrafine Rutile Titania Nanocrystallites in Hierarchical Nanotubular Silica/Titania Hybrids with Efficient Photocatalytic Activity

Abstract: Hierarchical-structured nanotubular silica/titania hybrids incorporated with particle-size-controllable ultrafine rutile titania nanocrystallites were realized by deposition of ultrathin titania sandwiched silica gel films onto each nanofiber of natural cellulose substances (e.g., common commercial filter paper) and subsequent flame burning in air. The rapid flame burning transforms the initially amorphous titania into rutile phase titania, and the silica gel films suppress the crystallite growth of rutile tit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 70 publications
0
21
0
Order By: Relevance
“…In particular, we have focused on the TiOSi stretching absorption bands in the 930–970 cm −1 region and the stretching absorption band at around 1050 cm −1 , which is attributed to SiOSi 18. 29 Beyond that, one can easily find that the intensities of the SiOSi bands become much stronger with increasing amounts of modified SiO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…In particular, we have focused on the TiOSi stretching absorption bands in the 930–970 cm −1 region and the stretching absorption band at around 1050 cm −1 , which is attributed to SiOSi 18. 29 Beyond that, one can easily find that the intensities of the SiOSi bands become much stronger with increasing amounts of modified SiO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the amount of rutile in TiFe25 is 36% and in TiFe35 is 73%, rest of the TiO 2 -Fe 2 O 3 composites (TiFe2-600, TiFe5-600, TiFe8-600, TiFe15-600) contain almost pure anatase phase TiO 2 . Anatase TiO 2 generally performs better in photocatalytic experiments as compared to rutile TiO 2 systems [26][27][28]. The superior performance of anatase over rutile in photocatalysis can be attributed to a number of factors, such as better charge-carrier mobility, lengthier exciton diffusion, bigger size of rutile particles and higher band gaps [27,28].…”
Section: X-ray Diffraction Studiesmentioning
confidence: 98%
“…The broad peaks inferred the nanoscale nature of the sample. [23] The crystal size, calculated assuming a (110) plane, was ~ 7.73 nm. This size was relatively smaller than the particle size measured in TEM images (10 nm), because the minor amorphous oleylamine layer was modified on the nanocrystal surface.…”
Section: Resultsmentioning
confidence: 99%